2020
DOI: 10.1007/s12144-020-01163-8
|View full text |Cite
|
Sign up to set email alerts
|

Unfriendly customer behaviors and employees’ psychological capital: the role of health symptoms and positive humor events

Abstract: This study examined mediators and moderators that may explain the link between unfriendly customer behaviors and workers' psychological capital with a sample of 380 employees. We hypothesized that perceived health symptoms would mediate the link between unfriendly customer behaviors and psychological capital. We also hypothesized a moderated mediation model, in which positive humor events would moderate the mediation model. Results show that the negative association between unfriendly customer behaviors with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…This is consistent with the humor-health hypothesis, which states that humor has beneficial effects for individual's optimal functioning [6]. Humor is globally recognized to be an indicator of positive mental health [7] and has been found to be related to both physical and psychological well-being [3]. However, this study goes further and specifies some conditions that may affect that relation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with the humor-health hypothesis, which states that humor has beneficial effects for individual's optimal functioning [6]. Humor is globally recognized to be an indicator of positive mental health [7] and has been found to be related to both physical and psychological well-being [3]. However, this study goes further and specifies some conditions that may affect that relation.…”
Section: Discussionsupporting
confidence: 84%
“…A potential reason for the full mediation found is that positive humor events facilitate the emergence of relaxation feelings, which contributes to increased levels of positive affect and, in turn, results in higher levels of well-being. Moreover, these results also emphasize the well-established concept that positive affect is a strong predictor of individual's well-being [7]. Thus, the more positive humor events, the higher the frequency of positive affect, which may be translated in higher levels of well-being.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…OECD (2019) has reported that workers appear to evidence lower levels of well‐being and satisfaction. These lower levels of well‐being affect the individual in many ways, for example, in the daily work‐related behavior and daily well‐being (Junça‐Silva & Lopes, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The use of humor is an effective coping strategy with social stressors (Junça-Silva and Lopes, 2020; Sliter et al. , 2014) and cabin crewmembers may engage in various forms of humor to tackle UPB.…”
Section: Theory and Hypothesesmentioning
confidence: 99%